New rationales for innovation policy?: a comparison of the systems of innovation policy approach and the neoclassical perspective - Alexandra Schröter (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Ever since its introduction in the 1990s, the systems of innovations (SI) concept has received a great deal of attention from researchers and politicians. The systems of innovation policy (SIP) approach, which is based on the SI concept, is considered an alternative to neoclassical theory. Its goal is to provide new rationales and criteria for innovation policy, as well as concrete implications and guidelines for policymakers, that are more appropriate for innovation processes in comparison to the rationales and criteria of standard economic theory. The aim of this paper is to critically investigate to what extent the SIP approach provides additional rationales for public intervention in innovation processes compared to neoclassical theory.
Keywords: O31; O38; P00; 330; Innovation; innovation systems; innovation policy; Innovationspolitik; Innovation; Systemtheorie; Neoklassik; Vergleich; Theorie